2020
DOI: 10.1039/c9ta11646j
|View full text |Cite
|
Sign up to set email alerts
|

Recent advancements in heterostructured interface engineering for hydrogen evolution reaction electrocatalysis

Abstract: Synthesis methods and catalytic properties of heterostructure catalysts for HER.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
141
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(141 citation statements)
references
References 227 publications
0
141
0
Order By: Relevance
“…The improvement in the catalytic activity of the ODR-Co 9 S 8 /CoO/NC in OER can be rationalized by rapid charge transfer and water dissociation induced by the generation of oxygen defects and the in situ formation of heterojunction [ 27 , 61 ]. Theoretical results have shown that the introduction of oxygen vacancies and heterojunction modulates the surface electronic structure of the catalysts by inducing denser electron density around the Fermi level, [ 62 , 63 ] where oxygen vacancies tend to generate inter-band states for improved conductivity and the formation of heterojunction remodels the d-band center to circumvent unwanted charge transfer resistance for fast reaction kinetics. Clearly, the ODR-Co 9 S 8 /CoO/NC heterostructure possessed the lowest η (217 mV), as compared to those of ZIF-67 (712 mV), Co 3 S 4 /Co(OH) 2 /ZIF-67 (335 mV), CoO/NC (367 mV), pure Co 9 S 8 (315 mV) and RuO 2 /C (290 mV).…”
Section: Resultsmentioning
confidence: 99%
“…The improvement in the catalytic activity of the ODR-Co 9 S 8 /CoO/NC in OER can be rationalized by rapid charge transfer and water dissociation induced by the generation of oxygen defects and the in situ formation of heterojunction [ 27 , 61 ]. Theoretical results have shown that the introduction of oxygen vacancies and heterojunction modulates the surface electronic structure of the catalysts by inducing denser electron density around the Fermi level, [ 62 , 63 ] where oxygen vacancies tend to generate inter-band states for improved conductivity and the formation of heterojunction remodels the d-band center to circumvent unwanted charge transfer resistance for fast reaction kinetics. Clearly, the ODR-Co 9 S 8 /CoO/NC heterostructure possessed the lowest η (217 mV), as compared to those of ZIF-67 (712 mV), Co 3 S 4 /Co(OH) 2 /ZIF-67 (335 mV), CoO/NC (367 mV), pure Co 9 S 8 (315 mV) and RuO 2 /C (290 mV).…”
Section: Resultsmentioning
confidence: 99%
“…HER process can produce high purity hydrogen, which is a new clean energy alternative with carbon‐free nature. However, the electrochemical production of H 2 is still not in industrial practice, mainly owing to the usage of precious metal catalysts to facilitate the HER kinetics [93–96] . Recent progress has demonstrated the great potential of transition metal based‐SACs for HER both experimentally and theoretically.…”
Section: Single‐atom Electrocatalysts Derived From Mofsmentioning
confidence: 99%
“…However, the electrochemical production of H 2 is still not in industrial practice, mainly owing to the usage of precious metal catalysts to facilitate the HER kinetics. [93][94][95][96] Recent progress has demonstrated the great potential of transition metal based-SACs for HER both experimentally and theoretically. Reproduced with permission.…”
Section: Sacs Derived From Mofs For Hermentioning
confidence: 99%
“…Hydrogen energy is regarded as the most promising alternative energy source to relieve energy crisis and environmental pollution, which two are inevitably a stumbling block to social development 1,2 , for the reason that it can be obtained at low cost and produce high energy on combustion with no air pollution [3][4][5][6][7][8] . However, the storage and transport of hydrogen are the main barriers when it comes to practical utilization 9,10 .…”
Section: Introductionmentioning
confidence: 99%